2022
DOI: 10.21873/invivo.13018
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery for Colorectal Cancer During the COVID-19 Pandemic in a Tertiary Medical Facility in Japan

Abstract: Background/Aim: The coronavirus disease 2019 pandemic has reduced hospital visits due to concerns regarding infection and also resulted in cancer screening delays. These changes may have had an impact on the progression of colorectal cancer (CRC). Therefore, the present study investigated the effects of the COVID-19 pandemic on minimally invasive surgery (MIS) for CRC using a correlation analysis of clinical outcomes before and during the COVID-19 pandemic. Patients and Methods: The present study targeted CRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…According to the analysis of hospital-based cancer registries, the number of colorectal cancer diagnoses, especially cases detected by screening, decreased in 2020 compared with the average number in the past four years [27] . Moreover, the decline in the diagnosis of early stage cancer during the pandemic was more pronounced than that of advanced cancers [27] , [28] , [29] , [32] , [36] . Our results show that endoscopic surgery, which is performed in patients with low-stage colorectal cancer, decreased during the pandemic, consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…According to the analysis of hospital-based cancer registries, the number of colorectal cancer diagnoses, especially cases detected by screening, decreased in 2020 compared with the average number in the past four years [27] . Moreover, the decline in the diagnosis of early stage cancer during the pandemic was more pronounced than that of advanced cancers [27] , [28] , [29] , [32] , [36] . Our results show that endoscopic surgery, which is performed in patients with low-stage colorectal cancer, decreased during the pandemic, consistent with the findings of previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have reported an upshift in staging during the pandemic period, demonstrating a decrease in early-stage disease and an increase in metastatic disease (Table 4). In a study comparing patients who underwent minimally invasive surgery for colorectal cancer before and during the COVID-19 pandemic, Kuodo et al [44] found a significantly higher number of cases with advanced tumor stage (pT4) in the COVID-19 group compared to the pre-COVID-19 group (P=0.026). Furthermore, the proportion of cases requiring combined resection of adjacent organs due to advanced T4 colorectal cancer was significantly greater in the COVID-19 group (16.4% vs. 4.4%, P=0.010).…”
Section: Changes In Tumor Stage and Oncological Variables Of Colorect...mentioning
confidence: 99%